ANALISA PENERAPAN ARSITEKTUR INDUSTRIAL PADA BANGUNAN KALLIA CAFE - Mulia, Endi Martha; Hutabarat, Marvin Frans Sakti; Chandra, Dennis; Stenli (Jurnal Sains dan Teknologi ISTP, 2025)
The development of the culinary industry in Indonesia plays an important role in the national economy. The development of the culinary coffee drink industry can also be seen in the many constructions of cafes or coffee shops. The cafe that is often found is a cafe with a luxurious feel so that it is expensive to maintain. For this reason, the concept of Industrial Architecture is a concept that emphasizes functional and efficient aspects by using unfinished materials but still considering design aesthetics, so as to reduce costs incurred. This research was conducted to see the application of industrial architectural characteristics to cafe buildings by conducting literature studies and linking them to case studies. The selected case study is the Kallia Cafe Cafe building, from this case study it will be analyzed by linking the case study data with the characteristics of Industrial Architecture. From this analysis, the results obtained are the application of the characteristics of the industrial architectural concept at Kallia Cafe in terms of exterior and interior.